2018
DOI: 10.1182/blood-2017-06-741033
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4: a moving target in immunotherapy

Abstract: CD28 and CTLA-4 are members of a family of immunoglobulin-related receptors that are responsible for various aspects of T-cell immune regulation. The family includes CD28, CTLA-4, and ICOS as well as other proteins, including PD-1, BTLA, and TIGIT. These receptors have both stimulatory (CD28, ICOS) and inhibitory roles (CTLA-4, PD-1, , and TIGIT) in T-cell function. Increasingly, these pathways are targeted as part of immune modulatory strategies to treat cancers, referred to generically as immune checkpoint b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
633
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 828 publications
(650 citation statements)
references
References 136 publications
(127 reference statements)
9
633
0
8
Order By: Relevance
“…36 CTLA-4 plays a critical negative regulatory role for T-cell function in the primary immune response. 37 We first found that the percentage of CTLA-4 + CD3 + , CD4 + and CD8 + T cells was significantly higher in patients with AML compared to healthy individuals ( Figure 1A and B). These results are similar to findings from a study of immune checkpoint protein expression on T cells from patients with chronic lymphocytic leukemia (CLL) in which higher numbers of CD4 + and CD8 + T cells with intracellular CTLA-4 were observed in CLL.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…36 CTLA-4 plays a critical negative regulatory role for T-cell function in the primary immune response. 37 We first found that the percentage of CTLA-4 + CD3 + , CD4 + and CD8 + T cells was significantly higher in patients with AML compared to healthy individuals ( Figure 1A and B). These results are similar to findings from a study of immune checkpoint protein expression on T cells from patients with chronic lymphocytic leukemia (CLL) in which higher numbers of CD4 + and CD8 + T cells with intracellular CTLA-4 were observed in CLL.…”
Section: Resultsmentioning
confidence: 82%
“…CTLA‐4 is a member of a family of immunoglobulin‐related receptors that have both stimulatory and inhibitory roles in T‐cell immunity . CTLA‐4 plays a critical negative regulatory role for T‐cell function in the primary immune response . We first found that the percentage of CTLA‐4 + CD3 + , CD4 + and CD8 + T cells was significantly higher in patients with AML compared to healthy individuals (Figure A and B).…”
Section: Resultsmentioning
confidence: 85%
“…A variant of cyclotide MCoTI‐II capable of binding to cytotoxic T lymphocyte‐associated antigen 4 (CTLA‐4) has been developed by the direct evolution method to target metastatic melanoma . CTLA‐4 is a type of immunoglobin receptor molecule expressed by T lymphocytes that serves as a checkpoint for several immune responses. It has been targeted earlier with monoclonal antibodies to elicit an immune‐mediated antitumor response.…”
Section: Cyclotide Scaffold For Anticancer Bioactive Peptidesmentioning
confidence: 99%
“…Although there are questions about the capacity of the intracellular domain of the CTLA‐4 receptor to transduce signals (and some suggestion that the influence of CTLA‐4 binding is limited to its own cycling between cytosolic vesicles and the cell surface), it has also been proposed that CTLA‐4 binding can antagonize the activation signal in a cell‐intrinsic manner by attenuating the PI3K pathway, by activating the protein phosphatase 2A (PP2A) …”
Section: Pi3kδ Downstream Of Checkpoint Receptorsmentioning
confidence: 99%